Letter - Borough of Paddington Labour Party and Trades Council, 7 May 1926 (Paddington)
1926-05-07 "Letter - Borough of Paddington Labour Party and Trades Council, 7 May 1926" [g0216001.jpg], 7 May 1926 Local Organisation